Peran Orangtua Terhadap Penanggulangan Kecanduan Gadget Pada Anak Usia Prasekolah - Maulidiyah Junnatul Azizah Heru; Atika Jatimi (Indonesian Health Science Journal, 2024)
Gadget addiction in children is a new phenomenon that causes long-term negative effects such as developmental delays, emotional imbalance and other negative impacts. Research purposes; This research was conducted with the aim of finding out the role of parents in overcoming gadget addiction in preschool children. Method; This research uses a qualitative approach with a descriptive case study type of research. This research was conducted from November to December 2023 in Selomukti Village, Mlandingan District, Situbondo Regency. The subjects in this research were 12 parents with children aged 3-6 years. This research focuses on informants based on certain categories using the interview method. The data analysis techniques used are data simplification, data presentation and drawing conclusions. Results;Parents play a role in the process of overcoming gadget addiction in preschool children by limiting the use of gadgets. Conclusion; The role of parents in limiting the use of gadgets in preschool children can reduce the negative impacts of gadget addiction